Political connections, overinvestment and governance mechanism in Indonesia - Mohammad Nasih; Admiralty SaAvira Al-Cholili; Iman Harymawan; Imran Haider; Nadia Klarita Rahayu (Cogent Economics & Finance, 2020)
The purpose of this study is to investigate the association between political connections and overinvestment in Indonesia as a democratic, multi-party and developing country. This study uses sample of 1,044 and 543 firm-year observations from listed firms on the Indonesian Stock Exchange from 2012 to 2017. A two-stage model is used to address overinvestment, which used two different measurements, then continued by ordinary least square regression to establish the main analysis result. This study finds that political connection is negatively associated with overinvestment in Indonesia. We also find that this negative association is increasing due to the existence of governance mechanism from both external and internal parties of the firm. Our results indicate that the significant negative associations between political connections with overinvestment, which later is strengthen by governance mechanism might be caused by several differences in institutional setting and/or political connections benefits between the previous research in China and with the place where this research is taken. This paper could give insights in decision-making for stakeholders to anticipate certain harmful issues to the companies that might be occurred by their politically connected top management like directors and commissioners.
Keywords: M40; M41; M48; 330; government mechanism; overinvestment; political connections